Eco-coalcrete : Waste-less earth, lively life - Norhaiza, Ghazali; Nur Farah Aziera, Jamaludin; Khairunisa, Muthusamy; Mohd Faizal, Md Jaafar; Fadzil, Mat Yahaya (2021)
The palm oil industry and coal industry produce a large number of wastes which disposed of and created environmental pollution. Global demand for natural aggregates for the production of concrete is projected to grow by an average of 7.7% per year to reach 66.2 billion metric tons by 2022 (Kuhar, 2014). Using coal bottom ash (CBA) as partial sand replacement and palm oil clinker (POC) as granite full replacement in ECO-COALCRETE would reduce the use of natural resources. ECO-COALCRETE give a beneficial effect on the environment by lessening the quantity of CBA and POC thrown on landfill sites. ECO-COALCRETE which contains lesser sand and no granite as compared to plain concrete is acceptable for structure.